The Influence of Perceived Organizational Culture and Transformational Leadership on Innovative Work Behavior PT.Sumber Cipta Multiniaga (DSO Jombang) - Suspahariati, Suspahariati; Khairani, Cut; Faizah, Naela Mikyalul; Raule, Jean Henry; Faizin, Faizin (PT. Hafasy Dwi Nawasena, 2024)
This study explores the influence of perceived organizational culture and transformational leadership on innovative work behavior, with additional multiple linear regression analysis. Involving 150 employees, the study adopted a quantitative descriptive approach with questionnaires as the main survey instrument. Although quantitative methods provide a measurable analytical framework, it is important to be mindful of some potential weaknesses, including bias in the measurement of complex constructs and the limitations of statistical analysis. The addition of multiple linear regression analysis allowed the researcher to evaluate the extent of the influence of perceived organizational culture and transformational leadership on innovative work behavior of PT. sumber cipta multiniaga (dso jombang) jointly, while controlling for other factors that might influence the results. However, interpretation of multiple linear regression requires caution, due to assumptions about linearity and independence between variables. The statistical analysis tool SPSS version 25 is also worth noting, especially in the context of this complex study. Multiple linear regression analysis may provide a deeper understanding of the dynamics of the relationships between variables, but a qualitative or mixed methods approach may be needed to capture deeper context and nuance. The results of this study highlight the importance of an innovation-supportive organizational culture, employee perceptions of the work environment, and the role of transformational leadership in driving innovative work behaviours. The practical implications include the potential development of more effective management strategies, but keep in mind that further research is needed to deepen the understanding of these complex dynamics. By combining holistic quantitative and qualitative approaches, future studies may make more substantial contributions to sustainable and innovative management practices.